A REVIEW OF LITERATURE’S CONTRIBUTION TO LINGUISTICS EDUCATION - Rasheed, Mohammed Hameed (Journal of Learning on History and Social Sciences, 2025)
Objective: This study investigates the integration of linguistic methods—specifically structuralist and semantic frameworks—into literary criticism to enhance textual interpretation and reader engagement. Method: A qualitative, descriptive-analytical approach was employed, analyzing selected English and Persian literary texts with a focus on phonological, grammatical, and semantic elements. Results: The findings reveal that linguistic features such as phoneme sequencing, grammatical ambiguity, and metaphorical language significantly shape reader response and thematic perception. Structuralist criticism deciphers formal patterns, while semantic analysis exposes deeper emotional and ideological layers within literary works. Novelty: The research offers a novel synthesis of linguistic and literary approaches, proposing a comprehensive, interdisciplinary model that bridges theoretical gaps and transcends disciplinary boundaries. This model advocates for a pedagogical shift in literature education, encouraging the use of linguistic tools to cultivate critical thinking and interpretive precision. The proposed framework demonstrates universal applicability across languages and genres, contributing both to the enrichment of literary scholarship and the advancement of curriculum development.